Unsur Intrinsik dan Nilai Moral dalam 5 Dongeng Anak Dunia: Kajian Struktural Sastra Anak: Intrinsic Elements and Moral Values in 5 Dongeng Anak Dunia: A Structural Study of Children's Literature - Habil, Ibnu; Mahmud, Teuku; Kasmi, Hendra (Program Studi Pendidikan Bahasa dan Sastra Fakultas Keguruan dan Ilmu Pendidikan Universitas Jambi, 2026)
This study analyzes the intrinsic elements in Dedik Dwi Prihatmoko’s book, “5 Dongeng Anak Dunia,” using a structural approach. The method employed is descriptive qualitative, utilizing literature review, note-taking, and documentation techniques. The results of the study indicate that all stories possess complete and systematic intrinsic elements (theme, plot, characters, setting, point of view, and style). Dominant themes include perseverance, harmony, mutual aid, kindness, and spirituality. The plot structure employs a simple and progressive narrative, animal characters with human-like traits, and a communicative and personificative writing style. The interconnection of these elements collectively reinforces the moral message. In conclusion, the folktales in this book are effective as a character education medium for early childhood and elementary school students and contribute to the development of a simultaneous structural analysis model.